2021
DOI: 10.1007/s00417-021-05294-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of neural networks to predict vault values after implantable collamer lens surgery

Abstract: Background Appropriate sizing of the implantable collamer lens (ICL) and accurate prediction of the vault are crucial prior to surgery. However, sometimes, the vault value is higher or lower than predicted, necessitating reoperation. The present study aimed to develop neural networks for improving predictions of vault values following ICL implantation based on preoperative biometric data. Methods This retrospective study included 137 eyes of 74 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…For concave shape iris, it had a tendency to demonstrate low vault value after ICL implantation; while for convex shape iris, most of eyes acquired a high vault value. With regards to the parameters about the lens, previous studies have reported that the LT and LR had significantly negative correlation with vault value in previous studies ( 10 , 11 , 19 , 20 ). However, eyes in our study obtained both high and low vault value even though they all had the LT > 4.0 mm.…”
Section: Discussionmentioning
confidence: 80%
“…For concave shape iris, it had a tendency to demonstrate low vault value after ICL implantation; while for convex shape iris, most of eyes acquired a high vault value. With regards to the parameters about the lens, previous studies have reported that the LT and LR had significantly negative correlation with vault value in previous studies ( 10 , 11 , 19 , 20 ). However, eyes in our study obtained both high and low vault value even though they all had the LT > 4.0 mm.…”
Section: Discussionmentioning
confidence: 80%
“…According to Kang et al [9] , these two measurements do not accurately reflect the size of the posterior chamber space in which the lens will be placed. The study by Xu et al [2] showed that although ATA distance does not use the sulcus diameter, it may be more accurate and reliable than other biometric parameters measured in the horizontal dimension. According to Igarashi et al [4] , ATA measurements had higher reproducibility than WTW measurements on AS-OCT, making them a more important predictor of a postoperative vault.…”
Section: Discussionmentioning
confidence: 99%
“…A Packer [16] meta-analysis showed that the STS-based formula is not superior to the WTW-based formula. Some additional factors, including investigator error, eye position, and anatomic changes in the ciliary sulcus, may affect the measurements [2] . In our patient, the horizontal STS size was 12.04 mm in the right eye and 11.43 mm in the left eye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Recently, machine learning regression of the preoperative AS-OCT metrics has been shown to provide higher predictability of the ICL vault than the conventional manufacturer's nomogram, and neural networks are reported to be applicable for vault predicting. 8,[14][15][16] The aim of this study was to develop a machine learning regression model and classifier to conveniently predict the ICL vault and size in daily practice by using AS-OCT (MS-39, Costruzione Strumenti Oftalmici) metrics and to compare the predictability outcomes with the online manufacturer's nomogram.…”
mentioning
confidence: 99%